Evaluating the use of Uromune® autovaccine in recurrent urinary tract infections: a pilot unicenter retrospective study in Reus, Spain - Simona Iftimie; Paula Ladero-Palacio; Ana F. López-Azcona; Laia Pujol-Galarza; Antoni Pont-Salvadó; Xavier Gabaldó-Barrios; Jorge Joven; Jordi Camps; Antoni Castro; Mercè Pascual-Queralt (BMC Infectious Diseases)
Abstract Background Urinary tract infections (UTIs) are a significant global health issue, especially among women, with growing concerns related to antibiotic resistance and adverse effects. The Uromune®, a sublingual, heat-inactivated, polybacterial vaccine, represents a promising therapeutic alternative by enhancing immune responses against uropathogens. Methods This pilot retrospective study, conducted at Hospital Universitari de Sant Joan de Reus from January 2018 to August 2022, assessed the association between Uromune® administration and changes in recurrent UTIs. Patients received personalized autovaccines administered as two sublingual puffs daily for three months. Clinical, microbiological, and demographic data were analyzed to assess treatment outcomes and identify recurrence-associated factors. Results Forty-nine patients (mean age, 61 years, and 59.2% women) were included in the study. Uromune® treatment decreased UTI episodes from 3.73 ± 0.97 the year before to 0.98 ± 1.36 (p < 0.001) the year after its administration. The number of patients who suffered three or more episodes per year dropped from 43 (87.7%) before the intervention to 7 (14.3%) afterwards. The maximum effectiveness of the autovaccine was observed three months post-administration, with 44 patients not experiencing any UTI episodes. Regression analysis identified having had a urostomy, chronic kidney disease, and being immunosuppressed as predictors of recurrence. Conclusion Uromune® autovaccine was associated with a significant reduction in the frequency of recurrent UTIs and related hospitalizations, offering substantial relief to patients. These findings suggest that Uromune® may be a promising option for managing recurrent UTIs, though controlled studies are needed to confirm its efficacy compared to standard treatments.